An Ecological Examination of Factors That Impact Well‐Being Among Developmentally‐Disabled Youth in the Juvenile Justice System. (June 2017) - Crosby, Shantel D.; Algood, Carl L.; Sayles, Brittany; Cubbage, Jayne
Abstract: Youth with developmental disabilities make up a large proportion of those in the juvenile justice system, and experience various unique and intricate threats to their well‐being. This review examines the complexity of these challenges, exploring the multiple levels of contextual factors that influence youth's well‐being as they experience adjudication. Using an ecological framework, this paper reviews findings on the individual socio‐demographic characteristics, as well as the micro, meso, exo, and macro factors that impact their development and functioning. Specific policy and practice implications are provided to address improving outcomes of youth in this population at each ecological level.